Comparative review of translational approaches in lipid-based and water-based encapsulation strategies for coenzyme Q10 - Norhamiza, Mohamad Sukri; Nadirah, Abd Rahim; El Enshasy, Hesham Ali; Aman Nor, Nor Farahiyah; Nur Izyan, Wan Azelee; Liza, Md Salleh; Zahir Husain, Kamari; Suhaila, Sujani; Nor Hasmaliana, Abdul Manas (2025)
The global coenzyme Q10 (CoQ10) market is expanding, driven by the increasing prevalence of chronic diseases, particularly cardiovascular disorders. Forecasts project a compound annual growth rate of 9.68% from 2025 to 2034. Despite its critical role in cellular energy metabolism and antioxidant defense, CoQ10’s clinical potential is constrained by poor water solubility and low oral bioavailability. This review delivers a critical and translational comparison of lipid-based and water-based encapsulation strategies, offering novel insights into their mechanistic advantages, formulation challenges, and clinical applicability for enhanced CoQ10 delivery. Lipid-based systems, such as self-emulsifying drug delivery systems (SEDDS), liposomes, and nanoemulsions, improve solubility and gastrointestinal absorption, protect CoQ10 from degradation, and promote lymphatic transport. However, they often require high excipient content and exhibit stability concerns, such as susceptibility to oxidation. Water-based approaches, including β-cyclodextrin complexation, polymeric nanoparticles, solid dispersions, and CoQ10–nicotinamide cocrystals, enhance aqueous solubility and absorption while offering better chemical stability and lower formulation cost. This review highlights the mechanistic differences, benefits, and limitations of each strategy, providing critical insights for the rational design of CoQ10 delivery systems. The findings support formulation optimization to improve therapeutic efficacy and inform manufacturing decisions for clinical and commercial applications. Looking ahead, future directions may include nano-enabled personalized medicine strategies based on individual metabolic profiles and the development of intranasal CoQ10 delivery platforms that leverage nanoscale lipid or water-based carriers for direct nose-to-brain transport in neurological disease therapy.